Functional communication training in the treatment of problem behavior maintained by access to rituals. Issue 3 (11th May 2014) - Rispoli, Mandy; Camargo, Síglia; Machalicek, Wendy; Lang, Russell; Sigafoos, Jeff
<x xml:space="preserve">Abstract</x> This study evaluated the assessment and treatment of problem behaviors related to rituals for children with autism. After functional analyses, we used a multiple‐probe design to examine the effects of functional communication training (FCT) plus extinction and schedule thinning as a treatment package for problem behavior and appropriate communication for 3 children. Results of the functional analyses suggested that problem behavior was maintained by reinstatement of the interrupted routine for all participants, and the treatment package reduced problem behavior. Generalization across activities was observed for 1 participant.